A scoping review on factors influencing milk consumption behavior among adults - Normawati Ahmad; Abu Bakar Rahman; Siti Nur Farhana Harun; Kamarulzaman Salleh; Noorlaile Jasman (Penerbit Universiti Kebangsaan Malaysia, 2023)
Introduction; Milk and dairy products are good sources of high-quality protein. Protein is important during weight loss and subsequent weight maintenance due to the high satiating effect which helps to prevent over-consumption of energy and thereby reduces body fat stores. Furthermore, dairy protein is a good source of essential amino acids for muscle protein synthesis and thus helps to maintain metabolically active muscle mass during weight loss. Regarding milk consumption, it is important to find the association between personal, environmental and behaviour factors with milk consumption. Objective; The aim of the study was to identify factors influencing milk consumption behaviour among adults. Methods; This study was based on the literature review and on different case studies from different parts of the world to fulfill the main scope of factors influencing milk consumption. Results; Based on this review, environmental factors were found to be the main influences on milk consumption behaviour, followed by personal factors and behaviour factors. Conclusion This review is also expected to enrich the documentation on the influencing of milk consumption behaviour among adults.